2020
DOI: 10.1136/bmjopen-2020-040547
|View full text |Cite
|
Sign up to set email alerts
|

Mask shortage during epidemics and pandemics: a scoping review of interventions to overcome limited supply

Abstract: ObjectiveTo characterise published evidence regarding preclinical and clinical interventions to overcome mask shortages during epidemics and pandemics.DesignSystematic scoping review.SettingsAll healthcare settings relevant to epidemics and pandemics.Search strategyEnglish peer-reviewed studies published from January 1995 to June 2020 were included. Literature was identified using four databases (Medline-OVID, EMBASE, CINAHL, Cochrane Library), forwards-and-backwards searching through Scopus and an extensive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
(152 reference statements)
0
16
0
Order By: Relevance
“…Given the intimate nature of direct care provision, there is an understanding that certain aspects of social distancing, for example working from home, are less applicable to the direct care environment. Therefore, the term physical distancing has been used in UK national IPC guidance [ 1 ]. The standard infection control precaution of physical distancing refers specifically to the actual measurable distance between two individuals while at work, within the health or other care environment.…”
Section: Resultsmentioning
confidence: 99%
“…Given the intimate nature of direct care provision, there is an understanding that certain aspects of social distancing, for example working from home, are less applicable to the direct care environment. Therefore, the term physical distancing has been used in UK national IPC guidance [ 1 ]. The standard infection control precaution of physical distancing refers specifically to the actual measurable distance between two individuals while at work, within the health or other care environment.…”
Section: Resultsmentioning
confidence: 99%
“…The WHO also recommended strategies to optimize the availability of personal protective equipment [ 19 ]. Kirubarajan et al [ 20 ] revealed numerous strategies that had been evaluated for overcoming a limited supply of personal protective equipment during pandemics or epidemics. They grouped the strategies into six main categories: (1) decontamination of disposable masks [ 21 , 22 , 23 ], (2) reuse and/or extended wear of disposable masks [ 24 , 25 , 26 , 27 ], (3) layering of masks [ 28 , 29 ], (4) introduction of reusable respirators [ 29 , 30 ], (5) use of non-traditional replacements or modifications to masks [ 31 , 32 ], and (6) use of stockpiled or expired masks [ 33 , 34 , 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using brand experience can increase consumers' willingness to pay for price premium [3]. During the period of the COVID-19 pandemic, the demand for PPE surged sharply, and the increase in the use of masks by ordinary people exacerbated the global supply shortage of masks [4][5][6], which led to the price surge [7,8]. Li et al [9] analyzed the reasons for the price fluctuation of masks during the epidemic period, including the relationship between short-term mask supply and demand, the imbalance between market supply and demand, the production cost of manufacturers, the hoarding of businesses, and the price fluctuation of masks, which is related to price increase and bid up.…”
Section: Literature Reviewmentioning
confidence: 99%